IMPLEMENTASI STRATEGI INDEX CARD MATCH UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PADA MATA PELAJARAN IPS - Nulinnaja, Ratna; Cholilah, Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The purpose of this study is to improve student activity and the value or learning outcomes in social studies subjects at SMPI Bani Hasyim Singosari obtained when the teacher implements the Index Card Match strategy. The method used by researchers is classroom action research, whose research consists of 2 cycles, and four stages including planning, implementing, observing, and reflecting. According to the pre-cycle percentage of student activity in social studies subjects only 45% of students are active in participating in the learning process with a score that is less than KKM. After carrying out the first cycle, obtained an increase in the percentage to 68% and the average learning outcomes obtained by students are 75 in accordance with KKM standards. Then the second cycle is carried out to maximize learning outcomes in social studies subjects. This cycle began a significant increase in the percentage of student activity to 90% and students were able to reach an average value of 85, which on average has exceeded the KKM standard. Thus it can be concluded that the use of the Index Card Match can be used sustainably in order to increase the activity and student learning outcomes.Keywords: learning strategies; active learning; educational goals